Analysis of 5G Standalone Security Against Man-in-the-Middle Attacks Using Sequence Number Desynchronization - An Nisa; Sopian soim; Lindawati (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2026)
The architecture of standalone 5G networks offers improved communication performance, but its authentication procedures remain vulnerable to eavesdropping threats. This research evaluates the system’s vulnerability to Man-in-the-Middle attacks and proposes comprehensive mitigation methods to address these security issues. Relying on Open5GS as the core network and UERANSIM as a simulator for base stations and user devices, testing was conducted in a virtualized environment. The methods used include traffic manipulation at the N2 interface to trigger desynchronization of the sequence number in the 5G-AKA authentication procedure. Experimental results show that packet interception successfully caused sequence number desynchronization, which directly led to authentication failure and device isolation due to Denial of Service. Additionally, network monitoring revealed that the HTTP/2 protocol displays customer data in plain text. In conclusion, Secure Socket Layer (SSL) encryption has proven effective as a mitigation method. With this integration, internal communication channels have been converted to a fully encrypted HTTPS format, preventing eavesdropping attempts. Furthermore, customer cryptographic parameters remain protected while keeping the operational overhead below acceptable limits.